A-207 Spatial Working Memory in Periadolescent Children: Preliminary Findings from the PRANK Study and Implications for Alzheimer's Disease & Down Syndrome. (17th August 2022) - Sexton, Jennifer; Ramirez, Meghan; Phipps, Connor; Heller, Abi; Behm, Lillian; Zatkalik, Abigail; Nickolas, Kristen; Maerlender, Arthur; Phatak, Vaishali; Cramer, Justin; Blair, James; Murman, Daniel; et al.
Abstract: Objective: Investigate spatial working memory (SWM) in typically developing periadolescent children (TDPC) as it relates to age and hippocampal volume (HV). Method: Using preliminary data from the Polygenic Risk for Alzheimer's disease in Nebraska Kids study (PRANK, R01 AG064247), we investigated the association between SWM, age, and HV. Our sample included TDPC (N=80, age 8-13 years), recruited from the community and tested at University of Nebraska Medical Center; demographics were consistent with the recruitment area. SWM was measured using the Spatial Working Memory task between error term from the Cambridge Neuropsychological Battery. Structural MRI data were collected using a 3T Siemens Prisma instrument. HV was measured using automated segmentation in Freesurfer (Fischl, 2012). Results: SWM was associated with age, r(80) = -.334, p = .002, such that older children showed fewer SWM errors than younger children. HV was not significantly associated with SWM, controlling for age, r(77) = -.027, p = .813. However, the direction of the relationship between HV and SWM (larger HV associated with fewer SWM errors) was consistent with previous literature (Faridi et al., 2015). Conclusions: These preliminary results suggest that increasing age is associated with better SWM in TDPC; findings for HV were non-significant. Although outside the scope of this analysis, we expect that our study's full sample will provide greater statistical power to test the association of SWM with HV. In future efforts, we will investigate this association as it relates to polygenic risk for Alzheimer's disease and whether these results generalize to children with Down syndrome.